Effect-site concentration of remifentanil during patient-controlled analgesia in labour. Issue 3 (August 2015) - Jost, A.; Blagus, R.; Ban, B.; Kamenik, M.
Highlights Intravenous remifentanil was used in patient-controlled analgesia for labour. Hypothetical effect-site remifentanil concentration (Minto's model) was examined. Higher value before contraction (residual value) resulted in lower pain score. Monitoring this parameter may be useful in future clinical practice. Confirmation with a pharmacokinetic model optimized for pregnant patients is required.